Олег Емельянович Кутафин и его "глава государства" : путь в историю - Поздняков, В. П.; Pozdnjakov, V. (My University, 2012)
The article deals with the problems of the formation of the state and legal philosophy in Russia in connection with the work of a full member of the Russian Academy of Sciences Oleg Emelyanovich Kutafin and the publication of his latest book, «Head of State». The focus is on the analysis of theoretical and methodological issues raised in the study of OE Kutafin. In particular focus is the consideration of Russian philosophical and legal thought of the 18th century.
Поздняков В. П. Олег Емельянович Кутафин и его "глава государства" : путь в историю / В. П. Поздняков // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 289-296.
Keywords: право; конституционализм; философия права; правовая методология; политика; монархия; республика; власть; глава государства; конституціоналізм; філософія права; правова методологія; політика; монархія; республіка; влада; голова держави; law; constitutionalism; the philosophy of law; legal methodology; politics; monarchy; republic; the power; the head of state